Barriers and Facilitators to Fruit and Vegetable Consumption Among Rural Indian Women of Reproductive Age. Issue 1 (March 2019) - Kehoe, Sarah H.; Dhurde, Varsha; Bhaise, Shilpa; Kale, Rashmi; Kumaran, Kalyanaraman; Gelli, Aulo; Rengalakshmi, R.; Lawrence, Wendy; Bloom, Ilse; Sahariah, Sirazul A.; Potdar, Ramesh D.; Fall, Caroline H. D.
Background: Micronutrient deficiencies have been a serious public health problem among women of reproductive age in low- and middle-income countries including India, adversely affecting maternal and child health and human capital outcomes. Fruit and vegetables are important sources of micronutrients, and consumption of these foods is less than recommendations. Objective: The objective of this study was to identify perceived barriers and facilitators to fruit and vegetable consumption among women of reproductive age living in rural communities in the State of Maharashtra, India. Methods: Women aged 18 to 40 years were recruited from 8 villages surrounding the city of Wardha, Maharashtra, India. We used qualitative methods and held 9 focus group discussions and 12 one-to-one interviews. The data collection was stopped when no new information emerged. We used inductive thematic coding to analyze the data. Results: Women knew that fruit and vegetables were beneficial to health and expressed that they wanted to increase the intake of these foods for themselves and their children. Seven main themes were identified as being barriers or facilitators to fruit and vegetable consumption: (1) personal factors, (2) household dynamics, (3) social and cultural norms, (4) workload, (5) time pressures, (6) environmental factors, and (7) cost. Conclusions: Rural Indian women consumed fruit and vegetables infrequently and said they would like to consume more. Several potentially modifiable factors affecting the intake of fruit and vegetables were identified. Value chain analyses of fruit and vegetables in these communities will be important to identify opportunities to intervene and increase consumption.